Pemikiran Haedar Nashir Tentang Moderasi dan Implikasinya pada Konsep Pendidikan Islam Berkemajuan - Wahyu Ramadan; Azaki Khoirudin (Fakultas Agama Islam Universitas Billfath, 2024)
Islamic education faces several opportunities and challenges in the current era of globalization and digitalization. As a preparatory effort to take advantage of opportunities and overcome existing obstacles, Islamic education needs to adopt the concept of moderation promoted by Haedar Nashir, namely upholding moderate Islamic norms. Thus, this research aims to analyze and describe Haedar Nashir's views on the concept of moderation and the implications of moderation for the concept of progressive Islamic education. The method used in this research is a qualitative approach using a literature study. According to Haedar Nashir's perspective, this study's results show that religious moderation is creating and bridging diversity to strengthen tolerant attitudes between religious communities. Religious moderation does not mean eliminating the value of faith, but developing a more open perspective. Second, the implication of religious moderation for progressive Islamic education, according to Haedar Nashir, is an effort to produce modern, intelligent, and devout human resources. Haedar Nashir also emphasized the urgency of human values, justice, and balance in progressive Islamic education.